New records for the genus Chimarra Stephens 1829 (Trichoptera: Philopotamidae) in India - Pandher, Manpreet Singh; Hussain, Zahid; Kaur, Simarjit; Parey, Sajad Hussain; Majeed, Aquib (Zootaxa, 2024)
Two new species records of genus Chimarra Stephens 1829 (Chimarra actinifera Schmid 1958 and Chimarra godagama Schmid 1958), both from Tamil Nadu, are added to the Philopotamidae fauna of India. Additionally, Chimarra subpositio Pandher et al. 2020 (nomen novum for Chimarra bicolor Navás 1932, a junior secondary homonym of Philopotamus bicolor Banks 1901, now in Chimarra) is redescribed and re-illustrated based on freshly collected material. With these new additions, and taxonomic changes, the genus Chimarra is represented by 57 species in India.